Separation Performance of Capillary Gas Chromatography Based on Monohydroxycucurbit[7]Uril Incorporated Into Sol–Gels as the Stationary Phase - He, Jing; Ran, Jingfeng; Yao, Jianmei; Zhang, Lingxue; Wang, Shasha; Wang, Yuan; Dong, Nan (Frontiers in Chemistry, 2020)
A novel monohydroxycucurbit[7]uril-based stationary phase for capillary gas chromatography (GC) has been produced. For this, a capillary column coating was made using a sol–gel technique, incorporating synthesized monohydroxycucurbit[7]uril (Q7OH) and hydroxy-terminated poly(dimethylsiloxane) (OH-PDMS) into the sol–gel network through hydrolysis and polycondensation and chemical sol–gel grafting to the inner wall of a fused-silica tube. The preparation method may produce a coating with greater integrity, which gives the prepared column a higher separation efficiency and better selectivity toward analytes than a reported stationary phase based on neat cucurbit[n]urils (Q[n]s). The prepared Q7OH/PDMS column had 3225 theoretical plates per meter determined using naphthalene at 120 ℃ and exhibited a weakly polar nature. The Q7OH/PDMS stationary phase achieved high resolution for a wide range of analytes with symmetrical peak shapes and showed advantages over a commercial stationary phase and a reported stationary phase based on neat Q[n]s that failed to resolve some critical analytes. Moreover, the column also showed good thermal stability up to 300 ℃ and separation repeatability with relative standard deviation values in the range of 0.01–0.11% for intraday, 0.11–0.32% for interday and 0.38–0.58% for column-to-column. In addition, the energy effect on the retention of analytes on the Q7OH/PDMS stationary phase was examined, showing that retention on the column was determined mainly by the enthalpy change. As demonstrated, the proposed coating method can address some disadvantages that exist with the reported Q[n]s columns and integrates the full advantages of Q7 and the sol–gel coating method while achieving outstanding GC separation performance.